A re-examination of feminist values and women’s attitudes towards marriage and childbearing - Ha, Pham Doan Trang (2010)
This research aims to address the gap in literature’s understanding of contemporary women’s attitude towards marriage and childbearing by re-examining what contemporary women define as “feminist” and consequently, the link between “feminist” values and women’s attitudes toward marriage and childbearing. Drawing on in-depth interview data, I find that feminist values as perceived by the respondents are not necessarily antagonistic or incompatible to traditional gender roles, and thus do not drive the respondents to reject family-formation and childbearing. Yet feminist values are still relevant in explaining the trend of delayed marriage and low fertility, as they cause the respondents to seek gender equality in marriage through financial independence. Consequently, despite seeing themselves as family-oriented and having strong desires for marriage and motherhood, the respondents exhibit career-orientedness in their future plans to work full-time and remain employed for several years, to delay marriage and to have less than two children.